PP.01.03: THE TWENTY FOUR HOURS AMBULATORY BLOOD PRESSURE MONITORING AS PREDICTOR OF SEVERE CORONARY ARTERY DISEASE IN PATIENTS WITH ACUTE CORONARY SINDROME WITHOUT PERSISTENT ST ELEVATION. (June 2015) - Soto, R.M.; Martínez, J.J.; Hernández, M.; García, Z.M.; Abellán-Huerta, J.; Abellán-Alemán, J.; Leal, M.; Rubio, R.; Soria, F.
Abstract : Objective: The aim of our study was to evaluate the information provided by the twenty four hours ambulatory blood pressure monitoring (ABPM), ankle-brachial index (ABI) and the pulse wave velocity (PWV) as predictors of severe coronary artery disease in patients with acute coronary síndrome (ACS) without persistent ST elevation. Design and method: All the patients hospitalized consecutively in Hospital SLucía (Cartagena) from Juanary to April 2014 were recruited. The ABPM, ABI and PWV were performed in the first 24 hours of hospitalization. Results: We recruited 60 patients. The average ABI value was 0.86 ± 0.25. Fifty-seven percent had an ABI<0.9 or >1.3. The average PWV was 11.6 ± 3.4 m/s. Sixty-seven percent had PWV>10 m/s. The average systolic blood pressure 24 h (SBP) was 124 ± 16 mmHg, the average diastolic blood pressure 24 h (DBP) was 68 ± 9 mmHg, the average daytime SBP was 125 ± 16 mmHg, the average daytime DBP was 69 ± 9 mmHg, the average nightime SBP was 120 ± 23 mmHg and the average nightime DBP was 64 ± 12 mmHg. The average variability of systolic blood pressure was 12 ± 3 mmHg. Thirteen percent had abnormal variability systolic blood pressure (>15 mmHg). Sixty-three percent had at least one hypotensive episode (value of SBP<100 mmHg). The average pulse pressure 24 h (PP 24 h) was 57 ± 13 mmHg. Fifty percent had an abnormal PP 24 h value (>55 mmHg). Most patients (85%) had abnormal circadian blood pressure patterns ("non-dippers" and "riser"). The patients with ABI<0.9 or >1.3 presented more frequently multivessel coronary disease. The SBP 24 h (r = 0, 50, p < 0, 01), daytime SBP (r = 0, 46, p < 0, 01), nightime SBP (r = 0, 39, p = 0, 01), maximum (r = 0, 45, p < 0, 01) and mínimum SBP (r = 0, 45, p < 0, 01), mínimum DBP (r = 0, 38, p = 0, 01), and the high early morning (r = 0, 46, p < 0, 01) were significantly associated (Spearman) with the presence of coronary disease in two or more vessels. We did not find significant association between PWV with the multivessel coronary disease. Conclusions: The presence of a variety of these abnormalities BP and peripheral arterial disease were found to be related with coronary artery disease extension or severity.